Implementation Of ‘Mudharabah’ Contracts And Their Impacts On Fund-Raising Products In Jambi Sharia Banking - Bahrul Ma'ani; Supyani -; Almusrijah Aini; Indah Maulinda (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
Funds with the ‘mudharabah’ principle are investment funds so that Islamic banks share the proceeds only to the owners of funds that use the ‘mudharabah’ principle. The collection of funds is applied to savings and deposit products that use ‘mudharabah’ contracts. The amount of income received by the owner of the ‘mudharabah’ fund is part of the income received in cash from the distribution of funds by Islamic banks. Therefore, the funds collected with the ‘mudharabah’ principle are one of the elements in calculating profit sharing. The problem raised in the research is how to implement the ‘mudharabah’ contract and its impact on fund-raising products in Islamic banking. Two main things affect the quality or results of research: the quality of research instruments and the quality of data collection. The quality of research instruments relates to the validity and reliability of the instruments and the quality of data collection regarding the accuracy of the methods used to collect data. Therefore, an instrument tested for validity and reliability may not necessarily produce valid and reliable data if the instrument is not appropriately used in collecting data. The type of research was the quantitative technique used through interviews, observations, and documentation. In analyzing the data obtained, the authors used descriptive techniques. The results showed that applying ‘mudharabah’ contracts to fund-raising products at Islamic banks is only applied to savings and deposit products, and the advantages of products that use ‘mudharabah’ contracts are basically to make it easier for customers to transact. These products can be used as financing guarantees. There are supporting and inhibiting factors in the products that use ‘mudharabah’ contracts. These supporting factors include the existence of Islamic sharia principles, which are used as a reference for implementing a profit-sharing system on all products, especially savings and deposit products, and the existence of infrastructure facilities within the company that are pretty complete. Meanwhile, the inhibiting factors include the lack of socialization regarding Islamic banks' existence. Abstrak: Dana dengan prinsip 'mudharabah' adalah dana investasi sehingga bank syariah membagi hasil hanya kepada pemilik dana yang menggunakan prinsip 'mudharabah'. Penghimpunan dana diterapkan pada tabungan dan deposito dengan akad mudharabah. Besarnya pendapatan yang diterima oleh pemilik dana mudharabah merupakan bagian dari pendapatan yang diterima secara tunai dari penyaluran dana oleh bank syariah. Oleh karena itu, dana yang dihimpun dengan prinsip 'mudharabah' menjadi salah satu unsur dalam menghitung bagi hasil. Masalah yang diangkat dalam penelitian ini adalah bagaimana penerapan akad mudharabah dan dampaknya terhadap penghimpunan dana di perbankan syariah. Dua hal utama yang mempengaruhi kualitas atau hasil penelitian: kualitas instrumen penelitian dan kualitas pengumpulan data. Kualitas instrumen penelitian berkaitan dengan validitas dan reliabilitas instrumen serta kualitas pengumpulan data mengenai ketepatan metode yang digunakan untuk mengumpulkan data. Jenis penelitian yang digunakan adalah teknik kuantitatif melalui wawancara, observasi, dan dokumentasi. Dalam menganalisis data yang diperoleh, penulis menggunakan teknik deskriptif. Hasil penelitian menunjukkan bahwa penerapan akad mudharabah pada produk penghimpunan dana di bank syariah hanya berlaku pada produk tabungan dan deposito, dan keunggulan produk yang menggunakan akad mudharabah pada dasarnya adalah untuk memudahkan nasabah dalam bertransaksi. Produk-produk ini dapat digunakan sebagai jaminan pembiayaan. Ada faktor pendukung dan penghambat dalam produk yang menggunakan akad mudharabah. Faktor pendukung tersebut antara lain adanya prinsip syariah Islam yang dijadikan acuan penerapan sistem bagi hasil pada semua produk khususnya produk tabungan dan deposito, serta adanya sarana prasarana di dalam perusahaan yang cukup lengkap. Sedangkan faktor penghambatnya antara lain kurangnya sosialisasi tentang keberadaan bank syariah. Kata-kata kunci: mudharabah, implementasi, dampak, produk penghimpunan dana, perbankan syariah.